ANALYZING THE USE OF CAPITAL LETTERS IN THE THESIS INTRODUCTION OF PGSD STUDENTS AT UNIVERSITAS RIAU - Meisy Edriana (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
The spelling mistakes looks simple but they affect the quality of writing. The accuracy of spelling measures a person’s language understanding. Making a mistake is a natural thing, but it does not mean that a writer ignores the rules in writing, especially in the use of capital letters. This study aimed to determine the use of capital letters in the thesis introduction of PGSD students at  Universitas  Riau. The method in this study was a quantitative descriptive method. The researcher selected 7 out of 13 rules of using capital letters stated in PUEBI (General Guidelines for Indonesian Spelling). The result showed that the overall average use of capital letters was 86.67 with a very good category.